Understanding the Eurovision Song Contest in Multicultural Australia We Got Love - Carniel, Jessica (Springer International Publishing, 2018)
This book presents the first in-depth study of the Eurovision Song Contest from an Australian perspective. Using a cultural studies approach, the study draws together fan interviews and surveys with media and textual analysis of the contest itself. In doing so, it begins to answer the question of why the European song contest appeals to viewers in Australia. It explores and challenges the dominant narrative that links Eurovision fandom to post-WWII European migration, arguing that this Eurocentric narrative presents a limited view of how contemporary Australian multicultural society operates in the context of globalized culture. It concludes with a consideration of the future of the Eurovision Song Contest as Australia enters into the 'Asian century'.